A versatile offset operator for the discrete observation of objects. (26th May 2021) - De Rosa, Sergio; Franco, Francesco; Petrone, Giuseppe; Casaburo, Alessandro; Marulo, Francesco
Abstract: The possibility of reconstructing the response of a system, starting from the response of a reference one, has always been a point of great interest in structural dynamics. This is proved by the increasing attention about the similitude and scaling methods, although the associated predictions are still not fully reliable. Therefore, the aim of this paper is to present a method aimed at defining a transformation matrix which links the outputs between two sets of points belonging to different linear systems. This matrix used for the transformation can be invoked for both deterministic and stochastic loads. As preliminary and validating test case, the reconstruction of the displacement responses of two plates subjected to deterministic load is presented. The results show that an exact estimation of the frequency response is achieved at the degrees of freedom used for defining the transformation, as expected.